2010
DOI: 10.1007/s00345-010-0514-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient age on outcome following bladder-preserving treatment for non-muscle-invasive bladder cancer

Abstract: Older age adversely affected the outcome of patients with NMIBC, which is particularly apparent in patients 80 years or older. Further prospective studies to confirm these findings are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…We first observed that treatment outcome was influenced by age, treatment scheme and tumour multifocallity, as showed in other reports (Bohle and Bock, 2004; Joudi et al , 2006; Fernandez-Gomez et al , 2008; Malmstrom et al , 2009; Kohjimoto et al , 2010; Ajili et al , 2012). To overcome the samples heterogeneity, these variables were taken into account in multivariate analysis models to assess the influence of tumour-associated glycans in BCG response.…”
Section: Discussionsupporting
confidence: 60%
“…We first observed that treatment outcome was influenced by age, treatment scheme and tumour multifocallity, as showed in other reports (Bohle and Bock, 2004; Joudi et al , 2006; Fernandez-Gomez et al , 2008; Malmstrom et al , 2009; Kohjimoto et al , 2010; Ajili et al , 2012). To overcome the samples heterogeneity, these variables were taken into account in multivariate analysis models to assess the influence of tumour-associated glycans in BCG response.…”
Section: Discussionsupporting
confidence: 60%
“…We previously reported that the bladder cancer recurrence risk was 2.3-fold higher for patients aged 80 years or older than those aged 60-69 years using a different cohort. 14 Joudi et al also reported that aging appeared to be associated with a decreased response to intravesical immunotherapy. 15 In fact, the factor of age is incorporated in the CUETO system, but not in the EORTC system.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Joudi et al reported, in a cohort of 412 patients with superficial BC treated with TURB plus BCG therapy, a 22% of difference in cancer free survival (CFS) among patients <70 years and >80 years (61% versus 39%, p=0.0002), with the latter that also reported a persistently lower response rate to BCG therapy [20]. Analougously, Kohjimoto et al, reported on 491 patients with non-muscle invasive BC treated with TURB followed by BCG therapy, an higher incidence of multiple and higher grades tumours in >70 patients and a lowest RFS (47.2%) and PFS (89.4%) at 2 year among >80 years patients, with a recurrence and progression risk of 2.3 and 2.8 times respectively higher compared to <70 years patients [21]. More recently, an European Organization for Reasearch and Treatment of Cancer (EORTC) trial, demonstrated, in 822 Ta-T1 patients treated with BCG or epirubicin and followed for a median of 9.2 years, a shorter time to progression, overall and cancer specific survival in patients >70 years, confirming the worse oncological outcomes in elderly patients [15].…”
Section: Discussionmentioning
confidence: 99%